Modified PET (Polyethylene Terephthalate) fiber as well as preparation method and application thereof in anti-sludge product

By performing alkaline activation and carbon chain silane hydrolysis on PET fibers, modified PET fibers are prepared, which solves the problem of easy pollution in outdoor environments, and achieves efficient anti-fouling ability and self-cleaning function, simplifies the process and reduces costs and environmental impacts.

CN119711172APending Publication Date: 2025-03-28TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411882413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

PET fibers are easily affected by moisture, silt and other pollutants in outdoor environments, resulting in surface pollution and affecting aesthetics and functionality. The use of surfactants in the prior art has problems such as increasing production costs, environmental pollution and process complexity.

Method used

By mixing PET fibers with alkali solution for activation treatment, and adding a solution containing carbon chain silane for hydrolysis, modifying PET fibers with good hydrophobicity is prepared, without the use of surfactants throughout the process.

Benefits of technology

The superhydrophobic properties of PET fibers are achieved, which significantly improves its anti-fouling ability, makes it self-cleaning function, reduces production costs and environmental impacts, and is simple and easy to produce on a large scale in industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711172A_ABST
    Figure CN119711172A_ABST
Patent Text Reader

Abstract

The invention provides a modified PET fiber and a preparation method thereof and application of the modified PET fiber in an anti-sludge product, the preparation method of the modified PET fiber comprises the following steps: S10, mixing PET fiber with an alkali solution to obtain a first mixed solution, activating the first mixed solution to obtain activated PET fiber, the mass concentration of the alkali solution is 0.1%-50%, and the mass concentration of the activated PET fiber is 0.1%-50%; the temperature of the activating treatment is 0-100 DEG C; and S20, mixing the activated PET fiber, a solution containing carbon chain silane and the aqueous alkali to obtain a second mixed solution, and hydrolyzing the second mixed solution at the temperature of 0-100 DEG C to obtain the modified PET fiber. According to the method, in the process of modifying the PET fiber, the modified PET fiber with good hydrophobicity can be obtained only by performing activation treatment through alkali liquor and then adding a carbon chain silane solution for functionalization treatment, the whole preparation process is simple in technology, no surfactant is needed, the pollution resistance of the material can be remarkably improved, accumulation of sludge on the surface of the material is reduced, and the service life of the material is prolonged. And the material has a self-cleaning function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to modified PET fiber, a preparation method thereof and application thereof in anti-sludge products. Background Art

[0002] PET fiber is a commonly used polymer material, widely used in textile, packaging and industrial fields. However, in practical applications, especially in outdoor environments, PET fiber is easily affected by moisture, sediment and other pollutants, resulting in surface contamination, affecting appearance and functionality. Therefore, how to improve the anti-sludge performance of PET fiber and enhance its hydrophobic self-cleaning effect has become a research hotspot in related technical fields.

[0003] In traditional material surface modification technology, in order to improve the uniform distribution of functional groups on the material surface, it is usually necessary to add surfactants such as CTAB (cetyltrimethylammonium bromide) in the process. This surfactant, when dissolved in water, Br - In free water, long-chain alkanes can be adsorbed on the surface of the fabric to make it positively charged, which makes it easier for the negatively charged hydroxyl groups to attack the ester groups in the fiber and promote the hydrolysis of the macromolecules. However, during alkali treatment, the alkali solution can directly participate in the hydrolysis reaction of the ester bonds of PET. By precisely controlling the temperature, alkali concentration and time, it is enough to form a rough structure of PET fibers and expose low surface energy groups. At the same time, PET fibers themselves contain hydrophobic aromatic rings (terephthalic acid groups) and long-chain alkyl groups (ethylene glycol parts). After alkali treatment, these hydrophobic groups may be exposed on their surface and play the role of surfactants in regulating the distribution of hydrophobic structures. In this case, the use of CTAB becomes redundant.

[0004] In addition, the surfactant may form an adsorption layer on the surface, which prevents the alkali solution from fully contacting the PET surface, thereby reducing the reaction efficiency. Surfactant residues may increase the surface energy, resulting in decreased hydrophobicity and durability. At the same time, the use of CTAB also brings many problems, including increased production costs, potential pollution to the environment, and increased process complexity, requiring stricter control of reaction conditions.

[0005] Based on the above technical problems, the present invention proposes a novel modified PET fiber, a preparation method thereof, and an application thereof in anti-sludge products. Summary of the invention

[0006] The present invention provides a method for preparing a modified PET fiber, the method comprising:

[0007] S10: mixing the PET fiber with an alkaline solution to obtain a first mixed solution, and performing an activation treatment on the first mixed solution to obtain an activated PET fiber, wherein the mass concentration of the alkaline solution is 0.1%-50%, and the temperature of the activation treatment is 0-100° C.;

[0008] S20: mixing the activated PET fiber, the solution containing carbon chain silane, and the alkaline solution to obtain a second mixed solution, and hydrolyzing the mixed solution to obtain the modified PET fiber, wherein the hydrolysis temperature is 0-100°C.

[0009] Therefore, in the preparation process of the modified PET fiber proposed by the present invention, only alkali solution is used for activation treatment, and then carbon chain silane solution is added for functionalization treatment to obtain a modified PET fiber with good hydrophobicity. The whole preparation process is simple, no surfactant is needed, and the raw materials are non-toxic, environmentally friendly, low-cost, and easy to produce on an industrial scale. The modified PET fiber proposed by the present invention can reduce the contact area between water and the surface of the material, and the water droplets can take away the particles on the surface of the material when rolling, especially in harsh environments such as rain and mud, which can significantly improve the material's anti-fouling ability, reduce the accumulation of sludge on the surface of the material, and make the material have a "self-cleaning" function.

[0010] According to some embodiments of the present invention, the number of carbon atoms in the carbosilane is 4-20. Thus, by making the number of carbon atoms in the above range, it is possible to ensure that the silane molecules have good chemical stability and adhesion during the surface modification process, and the super-hydrophobic properties of the PET fiber can be significantly improved by the hydrophobicity of the carbon chain. At the same time, the carbosilane within this range is easy to operate at room temperature, has mild reaction conditions, is suitable for industrial large-scale production, and can effectively reduce the release of volatile organic compounds, with environmental advantages.

[0011] According to some embodiments of the present invention, based on the total mass of the second mixed solution, the mass proportion of the alkaline compound in the second mixed solution is 0.001%-0.2%. Thus, this ratio range can effectively ensure that the concentration of the alkaline compound is moderate, which can not only fully activate the reaction sites on the surface of the material, promote the uniformity and effectiveness of the functionalization treatment, but also avoid potential damage to the material structure caused by high alkali concentration. At the same time, the design of this mass ratio reduces the corrosiveness of the reaction system, makes the process operation safer, reduces the subsequent cleaning steps, and enables the preparation to be completed in one step, thereby improving production efficiency and reducing costs.

[0012] According to some embodiments of the present invention, the carbon chain silane includes at least one of octadecyl trimethoxy silane and hexadecyl trimethoxy silane, thereby improving the hydrophobicity of the modified PET fiber and improving its stain resistance.

[0013] According to some embodiments of the present invention, the alkaline solution includes at least one of NaOH solution, KOH solution, LiOH solution, RbOH solution, CsOH solution, Ca(OH)2 solution, Sr(OH)2 solution, Ba(OH)2 solution, and ammonia solution.

[0014] According to some embodiments of the present invention, the activation treatment time is 10 min-720 min. Thus, this time range can ensure the flexibility of the activation treatment and meet the adaptability of different materials and specific process requirements.

[0015] According to some embodiments of the present invention, the hydrolysis time is 1 hour to 72 hours. Thus, this time range can ensure the adequacy of the hydrolysis reaction and provide flexibility for operations under different process conditions.

[0016] According to some embodiments of the present invention, the hydrolyzed PET fibers are washed, and the washing solvent includes at least one of water, methanol, ethanol, acetone, isopropanol, and tetrahydrofuran.

[0017] The second aspect of the present invention provides a modified PET fiber, which is prepared by the method provided by the first aspect of the present invention, and the water drop contact angle of the modified PET fiber is 135°-150°, thereby improving the anti-fouling performance of the modified PET fiber.

[0018] The third aspect of the present invention provides the use of the modified PET fiber provided in the second aspect of the present invention in anti-sludge products. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0020] Figure 1 This is a contact angle diagram of the original PET fiber without any treatment in Example 1 of the present application.

[0021] Figure 2 This is a contact angle diagram of PET fiber treated only with alkali solution in Example 1 of the present application.

[0022] Figure 3 This is a contact angle diagram of the modified PET fiber prepared in Example 1 of the present application.

[0023] Figure 4 This is a contact angle diagram of the modified PET fiber prepared in Example 2 of the present application.

[0024] Figure 5 This is a contact angle diagram of the modified PET fiber prepared in Example 3 of the present application.

[0025] Figure 6This is a contact angle diagram of the modified PET fiber prepared in Example 4 of the present application.

[0026] Figure 7 This is a contact angle diagram of the modified PET fiber prepared in Example 9 of the present application.

[0027] Figure 8 This is a diagram showing the anti-sludge performance test results of the original PET fiber without any treatment in Example 1 of the present application.

[0028] Fig. 9 This is a diagram showing the effect of the modified PET fiber prepared in Example 1 of the present application after being tested for its anti-sludge performance.

[0029] Fig.10 This is a diagram showing the effect of the modified PET fiber prepared in Example 3 of the present application after being tested for its anti-sludge performance.

[0030] Fig.11 This is a diagram showing the effect of the modified PET fiber prepared in Example 4 of the present application after being tested for its anti-sludge performance.

[0031] Fig.12 This is a diagram showing the effect of the modified PET fiber prepared in Example 5 of the present application after being tested for its anti-sludge performance.

[0032] Fig.13 This is a diagram showing the effect of the modified PET fiber prepared in Example 6 of the present application after being tested for its anti-sludge performance.

[0033] Fig.14 This is a diagram showing the effect of the modified PET fiber prepared in Example 7 of the present application after being tested for its anti-sludge performance.

[0034] Fig.15 This is a diagram showing the effect of the modified PET fiber prepared in Example 8 of the present application after being tested for its anti-sludge performance.

[0035] Fig.16 This is a diagram showing the effect of the modified PET fiber prepared in Example 9 of the present application after being tested for its anti-sludge performance.

[0036] Fig.17 The figure shows the effect of the modified PET fiber prepared in Example 1 of the present application after being repeatedly rubbed ten to fifteen times and then tested for anti-sludge performance.

[0037] Fig.18 The figure shows the effect of the modified PET fiber prepared in Example 12 of the present application after being repeatedly rubbed ten to fifteen times and then tested for its anti-sludge performance.

[0038] Fig.19 The figure shows the effect of the modified PET fiber prepared in Example 4 of the present application after being repeatedly rubbed ten to fifteen times and then tested for anti-sludge performance.

[0039] Fig. 20 The figure shows the effect of the modified PET fiber prepared in Example 13 of the present application after being repeatedly rubbed ten to fifteen times and then tested for its anti-sludge performance.

[0040] Fig.21 It is the Fourier transform infrared absorption spectrum of the modified PET fiber prepared in Example 1, Example 2, and Example 4 of the present application and the original PET fiber without any treatment. Specific implementation methods

[0042] The following examples further illustrate the specific implementation methods of the present invention, but the implementation methods of the present invention are not limited to these.

[0043] The present invention provides a method for preparing a modified PET fiber, the method comprising:

[0044] S10: Mixing the PET fiber with the alkaline solution to obtain a first mixed solution, and performing activation treatment on the first mixed solution

[0045] According to some embodiments of the present invention, PET fiber is mixed with an alkaline solution to obtain a first mixed solution, and the first mixed solution is activated to generate a large number of reaction sites on the fiber surface to obtain activated PET fiber, the mass concentration of the alkaline solution is 0.1%-50%, and the temperature of the activation treatment is 0-100°C.

[0046] As an example, the type of modified PET fiber is not limited, and may include, for example, at least one of conventional PET fiber, microfiber, nanofiber, porous fiber, hollow PET fiber, and coarse denier fiber.

[0047] According to some embodiments of the present invention, the mass concentration of the alkaline solution can be 0.1%, 1%, 10%, 20%, 30%, 40%, 50%, etc., or can be a range composed of any of the above numerical values. Thus, the reactivity of the alkaline solution and the material compatibility can be effectively regulated to ensure the uniformity and effect of the surface treatment. If the concentration of the alkaline solution is too low, the activation effect may be insufficient, resulting in fewer reaction sites on the material surface, thereby affecting the efficiency of subsequent functionalization treatments and the final performance of the material. If the concentration of the alkaline solution is too high, it may cause excessive corrosion to the material surface, damage the structural integrity of the material, and increase the difficulty of cleaning and the amount of solvent used, which may have an adverse effect on the environment and operational safety.

[0048] According to some embodiments of the present invention, the alkaline solution includes at least one of NaOH solution, KOH solution, LiOH solution, RbOH solution, CsOH solution, Ca(OH)2 solution, Sr(OH)2 solution, Ba(OH)2 solution, and ammonia solution.

[0049] According to some embodiments of the present invention, the activation treatment time is 10 min-720 min, for example, it can be 10 min, 100 min, 200 min, 300 min, 400 min, 500 min, 600 min, 720 min, etc., or it can be a range consisting of any of the above numerical values.

[0050] According to some embodiments of the present invention, the temperature of the activation treatment is 0-100°C, for example, 0°C, 20°C, 40°C, 60°C, 80°C, 100°C, etc., or a range consisting of any of the above values. If the temperature of the activation treatment is too low, the reaction rate may be significantly reduced, resulting in a prolonged activation treatment time and insufficient generation of surface reaction sites, thereby affecting the effect of subsequent functionalization treatment and the performance of the modified material; if the temperature of the activation treatment is too high, it may cause thermal damage to the material or degradation of the surface structure.

[0051] S20: Mixing the activated PET fiber, the solution containing carbon chain silane, and the alkaline solution to obtain a second mixed solution, and hydrolyzing to obtain the modified PET fiber

[0052] According to some embodiments of the present invention, the activated PET fiber, the solution containing carbon chain silane, and the alkaline solution are mixed to obtain a second mixed solution, which is hydrolyzed to introduce functional groups with low surface energy on the fiber surface to obtain the modified PET fiber, and the hydrolysis temperature is 0-100°C.

[0053] According to some embodiments of the present invention, the carbon chain of the carbon chain silane may further include F atoms, and the mass content of the F atoms may be 0.1%-20%.

[0054] According to some embodiments of the present invention, in the solution of carbosilane, the solvent may include at least one of water, methanol, ethanol, acetone, isopropanol, and tetrahydrofuran.

[0055] As an example, the hydrolysis temperature may be 0°C, 20°C, 40°C, 60°C, 80°C, 100°C, etc., or may be a range of any of the above values. If the hydrolysis temperature is too low, the silane chain is not fully hydrolyzed and cannot react with the surface active groups of the PET fiber, resulting in the PET fiber being unable to achieve the hydrophobic and anti-mud functions; if the hydrolysis temperature is too high, the alkaline solution will continue to react with the fiber to cause damage to the fiber structure, and the high temperature will accelerate the hydrolysis of silane, which may easily cause side reactions due to excessive concentration.

[0056] According to some embodiments of the present invention, the number of carbon atoms in the carbosilane is 4-20. For example, it can be 4, 8, 12, 16, 20, etc., or it can be the range composed of the above arbitrary numerical values. Thus, by making the number of carbon atoms in the above range, it is possible to ensure that the silane molecules have good chemical stability and adhesion during surface modification, and the super-hydrophobic properties of the material surface can be significantly improved by the hydrophobicity of the carbosilane. At the same time, the carbosilane within the scope is easy to operate at room temperature, and the reaction conditions are mild, suitable for industrial large-scale production, and can effectively reduce the release of volatile organic compounds, with environmental advantages.

[0057] If the number of carbon atoms is too small, the hydrophobicity of the silane molecule may be insufficient, making it difficult to effectively reduce the surface energy of the material surface, thus affecting the superhydrophobic performance. In addition, a carbon chain that is too short may lead to poor thermal stability of the molecule, affecting the durability and anti-fouling properties of the modified material; if the number of carbon atoms is too large, the volume of the silane molecule is too large, which may reduce its uniform distribution and adhesion on the material surface, while increasing the difficulty of dissolution during the reaction. An overly long carbon chain may lead to excessive accumulation of the material surface structure, affecting the final modification effect and increasing production costs.

[0058] According to some embodiments of the present invention, the carbon chain silane includes at least one of octadecyltrimethoxysilane and hexadecyltrimethoxysilane.

[0059] According to some embodiments of the present invention, based on the total mass of the second mixed solution, the mass proportion of the alkaline compound in the second mixed solution is 0.001%-0.2%. For example, it can be 0.001%, 0.01%, 0.1%, 0.15%, 0.2%, etc., or it can be a range composed of any of the above numerical values. Thus, this ratio range can effectively ensure that the concentration of the alkaline compound is moderate, which can not only fully activate the reaction sites on the surface of the material, promote the uniformity and effectiveness of the functionalization treatment, but also avoid potential damage to the material structure caused by high alkali concentration. At the same time, the design of this mass ratio reduces the corrosiveness of the reaction system, makes the process operation safer, reduces the subsequent cleaning steps, and enables the preparation to be completed in one step, thereby improving production efficiency and reducing costs.

[0060] If the mass proportion of the alkaline compound in the second mixed solution is too small, the reaction system may be unstable, the hydrolysis reaction may be incomplete, and the functional groups may be insufficiently generated, thus affecting the surface modification effect of the material; if the mass proportion of the alkaline compound in the second mixed solution is too large, the hydrolysis reaction is too intense, which not only reduces the controllability of the reaction, but also may trigger side reactions and generate unwanted products. Excessive alkali concentration may also cause corrosive damage to the surface of the substrate, affecting the structural integrity and performance stability of the material.

[0061] According to some embodiments of the present invention, the hydrolysis time is 1 h-72 h. For example, it can be 1 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h, 72 h, etc., or can be a range consisting of any of the above values.

[0062] According to some embodiments of the present invention, the method may further include washing and drying the hydrolyzed PET fibers, and the washing solvent includes at least one of water, methanol, ethanol, acetone, isopropanol, and tetrahydrofuran.

[0063] The drying temperature may be 25° C.-100° C., and the drying time may be 0.5 h-48 h.

[0064] Therefore, during the preparation process of the modified PET fiber proposed in the present invention, it only needs to be activated by alkali solution and then functionalized by adding carbon chain silane solution to obtain modified PET fiber with good hydrophobicity. The whole preparation process is simple, no surfactant is needed, and the raw materials are non-toxic, environmentally friendly, low-cost, and easy to produce on an industrial scale. The modified PET fiber proposed in the present invention can reduce the contact area between water and the surface of the material, and the water droplets can carry away the particles on the surface of the material when rolling, especially in harsh environments such as rain and mud, which can significantly improve the material's pollution resistance and reduce the accumulation of sludge on the surface of the material, so that the material has a "self-cleaning" function.

[0065] The second aspect of the present invention provides a modified PET fiber, which is prepared by the method provided by the first aspect of the present invention, and the water drop contact angle of the modified PET fiber is 135°-150°, thereby improving the anti-fouling performance of the modified PET fiber.

[0066] The third aspect of the present invention provides the use of the modified PET fiber provided in the second aspect of the present invention in anti-sludge products.

[0067] As an example, the modified PET fiber is suitable for various fields such as outdoor equipment, waterproof fabrics and daily clothing.

[0068] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0069] Example 1

[0070] Take a PET fiber cloth with a size of 5cm×25cm (see the contact angle diagram Figure 1), and then ultrasonically cleaned in deionized water and ethanol, with each cleaning time being 15 minutes. After cleaning, take out the fabric and dry it in an oven to ensure that the surface of the fabric is dry and clean. Weigh 2g of NaOH and dissolve it in 200mL of deionized water to prepare an alkaline solution. Heat the alkaline solution to 60°C in a water bath, and completely immerse the above-cleaned PET fiber fabric in the solution. Maintaining this temperature condition, perform alkaline treatment for 2 hours to activate the fiber surface and generate reaction sites. Measure 600μL of hexadecyltrimethoxysilane (HDTMS) and dissolve it in 225mL of ethanol and 60mL of deionized water. Afterwards, add 15mL of alkaline solution to the solution, mix and stir with a magnetic stirrer for 20 minutes to carry out a hydrolysis reaction to form a functionalized silane solution. The PET fiber fabric after alkaline treatment is taken out (see the contact angle diagram Figure 2 ), placed in the above functionalized silane solution, and subjected to magnetic stirring immersion treatment at room temperature for 18 hours, so that the surface of the fabric reacts with the low surface energy silane group to complete the functionalization treatment. After the immersion treatment is completed, the PET fiber fabric is taken out, and deionized water and ethanol are used to wash it successively to completely remove the reactants remaining on the surface of the fabric. After washing, the fabric is placed in an oven again for drying until it is completely dried, and finally a super-hydrophobic PET fiber fabric is obtained. The PET fiber fabric after the above treatment shows obvious super-hydrophobicity, reference Figure 3 , the water droplets formed a high contact angle of 140.2° on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0071] Example 2

[0072] The preparation method of the modified PET fiber is the same as that of Example 1, except that the PET fiber cloth after the alkali treatment is taken out, placed in the above-mentioned functionalized silane solution, and subjected to magnetic stirring immersion treatment at room temperature for 21 hours.

[0073] After the above treatment, the PET fiber cloth showed obvious super hydrophobicity. Figure 4 , the water droplets formed a high contact angle of 137.8° on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0074] Example 3

[0075] The preparation method of the modified PET fiber is the same as that of Example 1, except that the cleaned PET fiber is completely immersed in the alkaline solution and the alkaline treatment is carried out for 1.5 hours while maintaining the temperature.

[0076] After the above treatment, the PET fiber cloth showed obvious super hydrophobicity. Figure 5, the water droplets formed a high contact angle of 142.2° on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0077] Example 4

[0078] The preparation method of the modified PET fiber is the same as that of Example 1, except that the PET fiber cloth after the alkali treatment is taken out, placed in the above-mentioned functionalized silane solution, and subjected to magnetic stirring immersion treatment at room temperature for 24 hours.

[0079] After the above treatment, the PET fiber cloth showed obvious super hydrophobicity. Figure 6 , the water droplets formed a high contact angle of 142.5° on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0080] Example 5

[0081] The preparation method of the modified PET fiber is the same as that of Example 1, except that the cleaned PET fiber is completely immersed in the alkaline solution and the alkaline treatment is carried out for 4 hours at the same temperature. The PET fiber fabric after the alkaline treatment is taken out and placed in the above functionalized silane solution and subjected to magnetic stirring immersion treatment at room temperature for 18 hours.

[0082] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0083] Example 6

[0084] The preparation method of the modified PET fiber is the same as that of Example 1, except that the washed PET fiber is completely immersed in the alkaline solution and the alkaline treatment is carried out for 3 hours while maintaining the temperature.

[0085] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0086] Example 7

[0087] The preparation method of the modified PET fiber is the same as that of Example 1, except that 2.5 g of KOH is weighed and dissolved in 200 mL of deionized water to prepare an alkaline solution. The PET fiber fabric after the alkaline treatment is taken out and placed in the above functionalized silane solution for magnetic stirring immersion treatment at room temperature for 18 hours.

[0088] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0089] Example 8

[0090] The preparation method of modified PET fiber is the same as that of Example 1, except that a PET fiber cloth with a specification of 10×10 cm is taken and ultrasonically cleaned in deionized water and ethanol successively, and each cleaning time is 15 minutes. After cleaning, the cloth is taken out and dried in an oven to ensure that the surface of the cloth is dry and clean. 1.5 g of KOH is weighed and dissolved in 200 mL of deionized water to prepare an alkaline solution (i.e., the first solution). The first solution is placed in a water bath and heated to 60°C, and the above-cleaned PET fiber cloth is completely immersed in the solution. Under this temperature condition, the alkaline treatment is carried out for 1.5 hours.

[0091] The PET fiber fabric after the alkali treatment was taken out, placed in the above functionalized silane solution, and subjected to magnetic stirring immersion treatment at room temperature for 18 hours.

[0092] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0093] Example 9

[0094] The preparation method of the modified PET fiber is the same as that of Example 1, except that the cleaned PET fiber is completely immersed in the alkaline solution and the alkaline treatment is carried out for 3 hours at the same temperature. The PET fiber fabric after the alkaline treatment is taken out and placed in the above functionalized silane solution and subjected to magnetic stirring immersion treatment at room temperature for 21 hours.

[0095] After the above treatment, the PET fiber cloth showed obvious super hydrophobicity. Figure 7 , the water droplets formed a high contact angle of 142.9° on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0096] Example 10

[0097] The preparation method of the modified PET fiber is the same as that of Example 1, except that 600 μL of octadecyltrimethoxysilane (OTS) is measured and dissolved in 225 mL of ethanol and 60 mL of deionized water. The PET fiber fabric after the alkali treatment is taken out and placed in the above functionalized silane solution for magnetic stirring immersion treatment at room temperature for 21 hours.

[0098] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0099] Embodiment 11

[0100] The preparation method of the modified PET fiber is the same as that of Example 1, except that 600 μL of octadecyltrimethoxysilane (OTS) is measured and dissolved in 225 mL of ethanol and 60 mL of deionized water.

[0101] After the above treatment, the PET fiber cloth shows obvious superhydrophobicity, and water droplets form a high contact angle on the fiber surface, showing good self-cleaning effect and anti-sludge performance.

[0102] Example 12

[0103] The preparation method of modified PET fiber is the same as that of Example 1, except that 2.0 g NaOH and 0.025 g CTAB are weighed and dissolved in 200 mL deionized water to prepare an alkaline solution. 0.15 g NaOH and 600 μL hexadecyltrimethoxysilane (HDTMS) are weighed and dissolved in 225 mL ethanol and 75 mL deionized water. The PET fiber fabric after alkaline treatment is taken out and placed in the above functionalized silane solution for magnetic stirring immersion treatment at room temperature.

[0104] Embodiment 13

[0105] The preparation method of modified PET fiber is the same as that of Example 1, except that 2.0 g NaOH and 0.025 g CTAB are weighed and dissolved in 200 mL deionized water to prepare an alkaline solution. 0.15 g NaOH and 600 μL hexadecyltrimethoxysilane (HDTMS) are weighed and dissolved in 225 mL ethanol and 75 mL deionized water. The PET fiber fabric after alkaline treatment is taken out and placed in the above functionalized silane solution, and subjected to magnetic stirring immersion treatment at room temperature for 18 hours.

[0106] In this application, the contact angle test method is a static contact angle measurement method. The specific operation is as follows: Use a professional contact angle meter (such as an optical contact angle meter) to place the test sample flat on the sample table at room temperature. Use a micro-syringe to drip a certain volume (usually 5 μL) of deionized water droplets on the sample surface. After ensuring that the droplets are stable, the image of the side profile of the droplets is captured by the measuring instrument, and the contact angle between the droplets and the sample surface is analyzed and calculated. The contact angle test needs to be repeated at least 3 times, and measurement points at different positions are selected, and the average value is taken as the final contact angle of the sample. This method can accurately reflect the hydrophobic or hydrophilic properties of the sample surface and provide a scientific basis for the evaluation of material properties.

[0107] In this application, the anti-sludge performance is evaluated by the following test methods:

[0108] (1) Apply the mud-stain mixture to the center of the piece to be tested, and repeat the application 10 to 15 times until the mud-stain fully contacts and penetrates the fabric.

[0109] (2) placing the coated pieces in an oven to dry until completely dried;

[0110] (3) Allow the dried pieces to naturally return to room temperature;

[0111] (4) Use a toothbrush and running water to scrub the piece to be tested for about 1 minute. Do not use any detergent and do not rub it.

[0112] (5) Stop scrubbing when the stain no longer becomes noticeably lighter;

[0113] (6) Place the cleaned pieces in the oven again to dry until they are completely dry.

[0114] Repeated kneading process:

[0115] Place the prepared modified PET fiber sample at room temperature and rub the fiber repeatedly ten to fifteen times with hands or mechanical equipment. The force of each rubbing should be consistent and the direction should be the alternating warp and weft direction of the fiber to simulate the surface wear that may be caused by mechanical friction or external force during actual use.

[0116] The anti-sludge effect diagram of the modified PET fiber prepared in Example 1, Example 3-Example 9 is shown in Figure 8-Figure 16 ,Depend on Figure 8-Figure 16 It can be seen that the modified PET fiber prepared in the present application has good anti-sludge effect and no sludge residue.

[0117] Depend on Figure 17-Figure 20 It can be seen that after the modified PET fiber has been rubbed ten to fifteen times, its surface still exhibits excellent anti-sludge performance. Compared with the PET fiber treated with CTAB in the first step, the modified PET fiber prepared by the present invention without CTAB not only achieves efficient anti-sludge ability, but also exhibits more excellent durability. In the test after repeated rubbing, the modified PET fiber without CTAB can more effectively resist sludge adhesion, the sludge is easily removed, and the fiber surface remains clean. This shows that the present invention simplifies the process by omitting CTAB, while significantly improving the durability of the material, demonstrating outstanding innovation and practical application advantages.

[0118] Depend on Fig.21It can be seen that as the treatment time increases, the silicon-related signals on the PET surface have a tendency to increase significantly. Near 2300cm-1, the intensity of the Si-H bond signal gradually increases with time, from almost no signal in the blank sample (black curve) to the signal of the treated sample (red, blue, and green curves) increasing in sequence, indicating that the carbon chain silane compound gradually reacts chemically with the material surface. Similarly, the characteristic absorption peak of Si-O-Si has shifted significantly. From the blank sample (black curve) to the treated sample (red, blue, and green curves), the signal peak gradually moves toward the low wave number direction, indicating that as the hydrolysis reaction deepens, the content of Si-O-Si increases. This phenomenon shows that the hydrolysis time has a significant effect on the modification of the chemical structure of the PET fiber surface, and also verifies the effectiveness of the present invention in regulating the chemical environment of the fiber surface.

Claims

1. A method for preparing modified PET fiber, characterized in that: include S10: mixing the PET fiber with an alkaline solution to obtain a first mixed solution, and performing an activation treatment on the first mixed solution to obtain an activated PET fiber, wherein the mass concentration of the alkaline solution is 0.1%-50%, and the temperature of the activation treatment is 0-100° C.; S20: mixing the activated PET fiber, the solution containing carbon chain silane, and the alkaline solution to obtain a second mixed solution, and hydrolyzing the mixed solution to obtain the modified PET fiber, wherein the hydrolysis temperature is 0-100°C.

2. The method according to claim 1, characterized in that: The number of carbon atoms in the carbon chain silane is 4-20.

3. The method according to claim 2, characterized in that Based on the total mass of the second mixed liquid, the mass proportion of the alkaline compound in the second mixed liquid is 0.001%-0.2%.

4. The method according to claim 3, characterized in that The carbon chain silane includes at least one of octadecyltrimethoxysilane and hexadecyltrimethoxysilane.

5. The method according to any one of claims 1 to 4, characterized in that: The alkaline solution includes at least one of NaOH solution, KOH solution, LiOH solution, RbOH solution, CsOH solution, Ca(OH)2 solution, Sr(OH)2 solution, Ba(OH)2 solution, and ammonia solution.

6. The method according to any one of claims 1 to 4, characterized in that: The activation treatment time is 10 min-720 min.

7. The method according to any one of claims 1 to 4, characterized in that: The hydrolysis time is 1h-72h.

8. The method according to any one of claims 1 to 4, characterized in that: The hydrolyzed PET fibers are washed, and the washing solvent includes at least one of water, methanol, ethanol, acetone, isopropanol, and tetrahydrofuran.

9. A modified PET fiber, characterized in that: The modified PET fiber is prepared by the method according to any one of claims 1 to 8, and the water drop contact angle of the modified PET fiber is 135°-150°.

10. Use of the modified PET fiber according to claim 9 in anti-sludge products.

Citation Information

Patent Citations

  • Super-durable and super-hydrophobic textile and its making method

    CN103074768A

  • Method for carrying out super-hydrophobic modification on PET fabric surface

    CN103088629A

  • Surface modification method of polyester fiber fabric, modified polyester fiber fabric, and preparation method and application of rubber canvas composite material

    CN115613348A

  • Surface hydrophobic antibacterial composite fiber material and preparation method thereof

    CN116815501A

  • Method for preparing superhydrophobic filter material of bag-type dust collector and use thereof

    WO2022147860A1